2019
DOI: 10.1186/s13601-019-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunodominant IgE binding epitopes of Der p 24, a major allergen of Dermatophagoides pteronyssinus

Abstract: Background The identification of house dust mite (HDM) allergens and epitopes is important for allergy diagnosis and treatment. We sought to identify the Dermatophagoides pteronyssinus group 24 allergen (Der p 24) and to identify its immunodominant IgE epitope(s). Methods Der p 24 cDNA was cloned and expressed in a pET expression system. The IgE binding activity of purified recombinant (r)Der p 24 was evaluated by western blotting. Truncated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Mutation experiments are required to investigate the importance of the Lys 28 and Tyr 29 residues of Der f 24 for IgE-binding. The results of the present study were similar to that of homolog Der p 24, indicating that the major allergen Group 24 in HDM may share a similar dominant IgE epitope and produce similar clinical significance (25).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Mutation experiments are required to investigate the importance of the Lys 28 and Tyr 29 residues of Der f 24 for IgE-binding. The results of the present study were similar to that of homolog Der p 24, indicating that the major allergen Group 24 in HDM may share a similar dominant IgE epitope and produce similar clinical significance (25).…”
Section: Discussionsupporting
confidence: 81%
“…Previously, peptide-displaying phage technology and artificial synthesized peptide scanning technology have been used to identify immunodominant epitopes (37,40). Additionally, our previous study showed that the immunodominant IgE epitopes of Der p 24 located in the N-terminal 32-residue region triggered IgE production in vivo (25). In the present study, artificial hybrid proteins and synthesized polypeptides were used to identify the N-terminal region of Der f 24 as a major mediator of the IgE-binding activity of Der f 24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HDM‐specific IgE binds the high‐affinity IgE receptors on the surface of mast cells to make mast cells sensitized. Sensitized mast cells can be activated by re‐exposure to HDM allergens and release pro‐inflammatory mediators, such as histamine, leukotrienes, serotonin, and TNF‐α, to induce inflammation in the local tissues 4 . However, HDM still induces inflammation in the absence of mast cells or IgE receptor‐deficient 5 .…”
Section: Introductionmentioning
confidence: 99%